Studi Kritis Konsep Sunnah Muhammad Syahrur - Qaem Aulassyahied (Universitas Darussalam Gontor, 2015)
Sunna is one of Islamic legislation sources, more precisely it is positioned on the second position as a source of law. It’s also served as explanatory of the verses of the Qur’an. With this position, the existence of sunnah is very important in Islam. Unfortunately the movement to reject the truth of sunnah (ingkar sunnah) never fade. One figure who aggressively towards reconstruction concept of sunnah is Muhammad Syahrur. He proposed the concept of reading the text in accordance with the existence of the times, or also called by a contemporary readings text model. The problem is this concept results confusion in understanding religious texts. So if explored more deeply, the proposed concept by Syahrur is not appropriate when applied to understanding Islamic scientific literatures. This simple writing is trying to reveal in details of the confusion in Syahrur thought. The discussion will cite the arguments that are used by Syahrur in order to support the concept. The author tried to explain that Syahrur understanding toward arguments is not appropriate. Besides, the author also cites some of the opinions of scholars who criticize the concept of Syahrur. So that at the end of the discussion the confusion and discrepancy reading of the concept proposed by Syahrur will be revealed clearly.